High energy experimental proposals for the study of UNRUH (effect) radiation - Ispirian, K.A. (Вопросы атомной науки и техники, 2012)
After a short discussion on the physics of the Unruh effect, Hawking, Larmor and Unruh radiations we consider some experiments proposed up to 2008, which can be carried out with the help of high energy electron and optical or X-ray photon beams. Кратко обсудив физику эффекта Унру, излучения Хокинга, Лармора и Унру, мы рассматриваем некоторые из экспериментов, предложенных к 2008 году, которые могут быть проведены с помощью высокоэнергетичных пучков электронов и оптических либо рентгеновских фотонов. Після короткого обговорення фізики ефекту Унру, випромінювання Хокинга, Лармора та Унру, ми розглядаємо деякі з експериментів, що були запропоновані до 2008 року, які можуть бути проведені за допомогою високоенергетичних пучків електронів та оптичних або рентгенівських фотонів.